KITAB PEGON DAN PENANAMAN PRINSIP DASAR KEISLAMAN: Studi Kasus Kampung Santri Tarjumah di Tambangsari, Pati, Jawa Tengah - Moh Rosyid (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2020)
This article was written to description a hamlet that formed boarding school (pesantren), students (santri) local residents various places and local residents, there is mosque, pondok pesantren, al-Quran kindergarten, madrasah diniyah, kiai’s house, recitation system bandongan, use Kitab Tarjumah by pegon language, his work K.H Ahmad Rifa’i. Data of this research was gathered through interview, forum group discussion, and observation in Tambangsari hamlet, Kedungwinng village, Sukolilo subdistrict, Pati district, central Java. K.Rifa’i action against colonial named Rifa’iyah movement. The action creation Kitab Tarjumah make tauhid, fikih, and mistisisme. Now, passed on students (santri) who settled in his village. Her initial character K. Hannan now forwarded by generation. Observance of worship armed with religious knowledge by tradition recite so that it forms santri hamlet (kampung santri).